Low T3 syndrome is associated with 30-day mortality in adult patients with fulminant myocarditis - Miao, Guangrui; Pang, Shuo; Zhou, Yuanhang; Duan, Mingxuan; Bai, Linpeng; Zhao, Xiaoyan (Frontiers in Endocrinology, 2023)
Background: Fulminant myocarditis (FM) is a critical disease with high early mortality. Low triiodothyronine syndrome (LT3S) was a strong predictor of poor prognosis of critical diseases. This study investigated whether LT3S was associated with 30-day mortality in FM patients. Methods: Ninety-six FM patients were divided into LT3S (n=39, 40%) and normal free triiodothyronine (FT3) (n=57, 60%) groups based on serum FT3 level. Univariable and multivariable logistic regression analyses were performed to identify independent predictors of 30-day mortality. Kaplan–Meier curve was used to compare 30-day mortality between two groups. Receiver operating characteristic (ROC) curve and decision curve analysis (DCA) were used to assess the value of FT3 level for 30-day mortality prediction. Results: Compared to normal FT3 group, LT3S group had higher incidence of ventricular arrhythmias, worse hemodynamics, worse cardiac function, more severe kidney impairment, and higher 30-day mortality (48.7% vs. 12.3%, P<0.001). In univariable analysis, LT3S (odds ratio [OR]:6.786, 95% confidence interval [CI]:2.472-18.629, P<0.001) and serum FT3 (OR:0.272, 95%CI:0.139-0.532, P<0.001) were significant strong predictors of 30-day mortality. After adjustment for confounders in multivariable analysis, LT3S (OR:3.409, 95%CI:1.019-11.413, P=0.047) and serum FT3 (OR:0.408, 95%CI:0.199-0.837, P=0.014) remained independent 30-day mortality predictors. The area under the ROC curve of FT3 level was 0.774 (cut-off: 3.58, sensitivity: 88.46%, specificity: 62.86%). In DCA, FT3 level showed good clinical-application value for 30-day mortality prediction. Conclusions: In FM patients, LT3S could independently predict 30-day mortality. FT3 level was a strong 30-day mortality predictor and a potentially useful risk-stratification biomarker.